Accelerated corrosion of silicon carbide in hypersonic plasmas with water vapor species. Issue 2 (15th January 2022) - Zhao, Changhao; Yang, Lingwei; Xiao, Xueren; Wang, Guolin; Zhang, Jun; Luo, Jie
Abstract: A novel technique was proposed in this work to generate hypersonic water vapor plasmas in an inductively coupled plasma wind tunnel. Based on it, the oxidation behavior of a typical SiC coating was studied at varying heat flux in reduced pressure. The key observation is an accelerated corrosion of the SiC coating at <1300 °C in the water vapor plasmas, which further triggered its early rupture from the beneath graphite substrate. The failure temperature was much lower than that in pure air plasmas. The corrosion mechanism was discussed by comparing the oxidation behaviors in both air and water vapor plasmas. It is inferred that the SiC corrosion was mainly a consequence of the reactivity of the as-formed SiO2 with water vapor species. As a result, the thermal balance was hardly achieved on the oxidized surface, and the oxidation temperature was fluctuated. As the corrosion proceeded in water vapor plasmas, the SiC coating was finally peeled-off due to ablation of the beneath graphite.